Legal Analysis of the Rehabilitation Decision for Narcotics Abusers in District Court Decision Number 43/Pid.Sus/2022/PN Jkt.Brt - Rochman, Arif; Setiawan, Herman (SALAM: Jurnal Sosial dan Budaya Syar-i, 2024)
Drug abuse has a disturbing impact on society and is a serious concern in efforts to combat illicit drug trafficking in Indonesia. Drug addicts are victims who require special treatment through rehabilitation, as regulated in laws and regulations. In this context, the authority of judges to decide on rehabilitation for drug addicts is interesting to study.This study aims to analyze the legal regulations on rehabilitation for drug addicts and the basis for the considerations of the Panel of Judges in issuing a rehabilitation decision in the District Court Decision Number 43/Pid.Sus/2022/PN Jkt.Brt. The research method used is normative juridical, with a focus on the application of positive legal norms in the case.The results of the study show that the legal regulations on rehabilitation for drug addicts are regulated in Article 1, number 16 of Law No. 35 of 2009 concerning Narcotics. Medical rehabilitation is carried out in hospitals appointed by the government or private hospitals that have obtained permission from the Minister of Health. The Panel of Judges in Decision Number 43/Pid.Sus/2022/PN Jkt.Brt based its considerations on TAT Recommendation Number R/64/X/TAT/2021/BNNP dated October 21, 2021, on behalf of the defendant Thomas Sondegau, ST, which stipulated four months of outpatient rehabilitation at the BNNP DKI Jakarta. This consideration also refers to Article 54 of the Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics, which requires drug addicts to undergo medical and social rehabilitation.Keywords: Rehabilitation, Drug Addicts, Narcotics